Photojournalism in the age of artificial intelligence: new challenges and opportunities - Gurtovaya, Ekaterina A. (Journal of the Belarusian State University. Journalism, 2024)
The article examines the influence of artificial intelligence (AI) technologies on the functioning of modern photojournalism. Based on a study of publicly available editorial standards, rules for well-known photojournalism competitions, domestic and foreign scientific works, as well as publications in the media, current names of images generated using AI were identified, and some current approaches to the use of AI algorithms in editorial work were named. A study of Belarusian online media and their Тelegram channels (n = 40) for 2023 – June 2024 made it possible to establish the features of the use of AI when working with images in Belarusian media practice. The constructive possibilities and risks of using AI technologies in the field of photojournalism are identified.